2009
DOI: 10.1080/02791072.2009.10400535
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Coherence as a Stable Predictor for Methadone Maintenance Treatment (MMT) Outcome

Abstract: We studied stability of sense of coherence (SOC) over time and in relation to the outcomes of former heroin addicts in MMT. Between September of 2003 and April of 2006, all 90 newly admitted patients to a MMT clinic in Tel Aviv were studied and followed up for one year. A SOC (inner resources) questionnaire was done at baseline and after one year. Use of opiates, cocaine, benzodiazepines, cannabis and amphetamines in the 13 months after admission was recorded, and defined as positive if at least one urine test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
2
16
0
1
Order By: Relevance
“…Abramsohn, Peles, Potik, Schreiber, & Adelson, (2009) reported that a greater sense of coherence was associated with longer retention in treatment. A surprising result was that stages of change were not related to treatment retention in the present study, even when more stringent criteria were applied to categorize participants into a clearly defined stage of change (see Secondary analysis).…”
Section: Discussionmentioning
confidence: 99%
“…Abramsohn, Peles, Potik, Schreiber, & Adelson, (2009) reported that a greater sense of coherence was associated with longer retention in treatment. A surprising result was that stages of change were not related to treatment retention in the present study, even when more stringent criteria were applied to categorize participants into a clearly defined stage of change (see Secondary analysis).…”
Section: Discussionmentioning
confidence: 99%
“…For example, SOC was found to be a strong protective factor, explaining negative attitudes toward alcohol consumption and drug abuse among high school students (Sagy, Shani, & Leibovich, ). A strong SOC is also related to positive intervention outcomes in rehabilitation programs (Abramsohn, Peles, Potick, Schreiber, & Adelson, ), while a weak SOC is typical among drug addicts (Chen, ). SOC was also indicated as meaningful in the context of interpersonal violence.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who abused drugs only once (at study entry or at follow-up) or did not abuse at all had longer cumulative retention compared to patients who abused drugs both at study entry and during the follow-up. As had been indicated in previous studies, drug abstinence constitutes a reliable and accurate measurement of MMT success, and it could serve as a predictor for treatment outcome (Abramsohn et al 2009;Peles, Schreiber & Adelson 2006).…”
Section: Vulnerable Attachment Among Mmt Patientsmentioning
confidence: 63%